2011
DOI: 10.1111/j.1467-9701.2011.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

China’s Macroeconomic Imbalances: Causes and Consequences

Abstract: In recent years, China has experienced two forms of extreme macroeconomic imbalance: an expenditure imbalance in the sense of very high investment and very low consumption, giving rise to rapid capital accumulation; and an imbalance between expenditure and production, producing external imbalance, i.e. a huge surplus on the current account of the balance of payments. Both imbalances imply a low rate of time discount by both government and society: consumption in the present is forgone in favour of consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The share of domestic content in China's processing exports has been increasing recently. Knight and Wang () reported that China's high investment levels in recent years have enabled firms to substitute foreign sources of intermediate products with domestic sources. Kuijs () observed that China has developed deeper supply chains in the processing sector and that more of the value added of processed exports can now be produced in China.…”
Section: Resultsmentioning
confidence: 99%
“…The share of domestic content in China's processing exports has been increasing recently. Knight and Wang () reported that China's high investment levels in recent years have enabled firms to substitute foreign sources of intermediate products with domestic sources. Kuijs () observed that China has developed deeper supply chains in the processing sector and that more of the value added of processed exports can now be produced in China.…”
Section: Resultsmentioning
confidence: 99%
“…but by the persistent decrease in the households' share of national disposable income' (Ivanova 2011: 867; for empirical support of this assertion see Aziz and Cui 2007). Importantly, most studies of China's evolving savings structure show that government and especially corporate savings -usually defined as corporate profits minus dividends -have been the key driver of its rising aggregate savings (Kuijs 2006;Knight and Wang 2011;Ma and Yi 2010; Figure 3). Given that government savings have increased largely as a result of the steady rise in government revenue linked to the investment-led economic expansion, China's saving structure reflects the declining share of household income and consumption …”
Section: Chinese Monetary Powermentioning
confidence: 89%
“…Overcapacity leads to a shortage of adequate investment channels in the 'real' economy, thus making available excess liquidity for 'financial' transactions in the stock market and the real estate market (Chen 2008;Sun and Zhang 2008). As a result, the surge in surplus liquidity associated with massive reserve accumulation coincided with the development of bubbles in both the stock and real estate markets: between 2004 and 2009 average house prices in China's 35 main cities tripled, whereas the Shanghai comprehensive stock index surged from 998 in July to 6212 in October 2007 (Knight and Wang 2011).…”
Section: Surplus Monetary Liquidity Soe Investments and Financial Frmentioning
confidence: 96%
“…Following this argument, the mainstream literature focuses on the causes of the excess foreign exchange reserves (international reserves). China's export-led strategy builds up a large current account surplus, which is interpreted as strong economic fundamentals and attracts intensive capital inflows (Knight & Wang, 2011;Zhang, 2009). These twin surpluses build up foreign exchange reserves to high levels (Chen, 2008).…”
Section: Excess Reserves: Sources and Theorymentioning
confidence: 98%